k+3-2/3k=67/24

Simple and best practice solution for k+3-2/3k=67/24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k+3-2/3k=67/24 equation:


k in (-oo:+oo)

k-((2/3)*k)+3 = 67/24 // - 67/24

k-((2/3)*k)-(67/24)+3 = 0

k+(-2/3)*k-67/24+3 = 0

1/3*k+5/24 = 0 // - 5/24

1/3*k = -5/24 // : 1/3

k = -5/24/1/3

k = -5/8

k = -5/8

See similar equations:

| -1/7-5a+7a=153/7 | | -9-k+1/3k=-17 | | x^2/7=2x-7 | | 6/7t+1/7-2/3t=19/77 | | 5+5/6d+5d=75 | | 2/7w-1+w=-115/7 | | 6m+1+7m=-103 | | 1/2n+10+n=35/2 | | 7t+7/8+5t=-787/88 | | 4x+9=8x+13 | | -5w-6-3w=-94 | | -282/5=4/5m-6m+6 | | -4/5k-4/7+2/5k=-82/315 | | 3/4-1/2w+6w=16/3 | | -1/3x+7+3x=16/3 | | 7/8=3b+6b+7/8 | | a+2/3+3a=14/3 | | 4n-5/6+3n=289/6 | | 5+7t+t=103/11 | | -1/2b+8/9+4/7b=374/441 | | -1/3+2/3k-2k=-5/3 | | 1/3k-2/9-5k=-2/9 | | 2/3k-1/2-k=-17/6 | | 1/2d+1/2-5d=11/4 | | -6/7d-6+2/3d=-204/35 | | 10+1/3m+3m=310/33 | | 45/56=2w-7w-5/8 | | 5+5k-k=-7 | | 1/5+2/7b+2b=237/385 | | 1/5m+3/5-m=-1/15 | | -71/21=-4n+3/7n-1 | | -1+4/7k+6k=29/63 |

Equations solver categories